Use of Extracorporeal Membrane Oxygenation for Major Cardiopulmonary Resections - Koryllos, Aris; Lopez-Pastorini, Alberto; Galetin, Thomas; Defosse, Jerome; Strassmann, Stephan; Karagiannidis, Christian; Stoelben, Erich (The Thoracic and Cardiovascular Surgeon, 2020)
Background In thoracic surgery, utilization of extracorporeal membrane oxygenation (ECMO) is mainly established for patients undergoing lung transplantation. The aim of our study was to summarize our single-center experience with intraoperative use of veno-venous- or veno-arterial-ECMO in patients undergoing complex lung surgery involving the main carina, or the left atrium or the descending aorta.Methods A total of 24 patients underwent combined complex lung, carinal, aortal, or left atrial resections. In cases of carinal resection, percutaneous veno-venous, jugular–femoral cannulation was considered suitable. For combined resection of lung and descending aorta, a percutaneous femoral veno-arterial cannulation was used. In cases of extended left atrial resection, a percutaneous jugular–femoral veno-venous-arterial cannulation was favored.Results Procedures were divided into three groups: carinal resections and reconstruction (n = 8), resections of the descending aorta and left lung (n = 7), resections of lung and left atrium (n = 9). No intraoperative complications occurred. Overall 30-day mortality was 25%. A complete resection was achieved in 18 patients. Median survival was 12 months. One- and 5-year survival were 48.1 and 22.7%, respectively.Conclusion The present study shows that intraoperative use of ECMO for extended carinal, aortic, or atrial resections is feasible with minimal intraoperative complications allowing surgeons increased operating-field safety. Perioperative mortality is high, but this is rather an attribute of local extended disease and patient comorbidities.
Keywords: extracorporeal membrane oxygenation; ECMO; aorta/aortic; airway